THE BLUE-HALAL-REGIONAL NEXUS: A MODEL FOR SUSTAINABLE ARCHIPELAGIC DEVELOPMENT IN THE BANGKA BELITUNG ISLANDS - Ahmad Yani; Yogi Cahyo Ginanjar (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the interaction between blue economy development, regional economic transformation, and Islamic economic principles in shaping sustainable growth in the Bangka Belitung Islands. Using a qualitative-descriptive approach supported by GRDP data from 2020–2024 and policy documents from BPS, KKP, BI, and KNEKS, the analysis highlights how the province is transitioning from a mining-dependent economy to a more diversified maritime system. The findings show that key blue economy sectors, fisheries, manufacturing, maritime logistics, and tourism, exhibit stronger growth and resilience compared to mining, particularly during the post-pandemic recovery period. These sectors collectively contribute approximately 35% of the province’s GRDP, with absolute values rising significantly from IDR 54.65 trillion in 2020 to 75.77 trillion in 2024, indicating deepening structural integration of ocean-based economic activities. In parallel, Islamic economic instruments play an increasingly vital role in supporting inclusive and ethical development. Mechanisms such as mudarabah, musharakah, qardhul hasan, and productive waqf have expanded financing access for coastal MSMEs, strengthened micro-level resilience, and facilitated value-added activities in fisheries, processing industries, and marine tourism. These practices align with maqasid al-shariah principles, ensuring that economic growth is pursued alongside social justice and environmental responsibility. The integration of blue economy strategies and Islamic economic ethics forms a coherent framework for sustainable regional development. This research proposes the “Blue–Halal–Regional Nexus” as a conceptual model that synthesizes environmental stewardship, inclusive finance, and spatial competitiveness. The study’s findings offer important insights for policymakers seeking to accelerate structural transformation and build resilient archipelagic economies in Indonesia and beyond.